Strong-field effects in the photoemission spectrum of the C60 fullerene - Gao, C. Z.; Dinh, P. M.; Klüpfel, P.; Meier, C.; Reinhard, Paul-Gerhard; Suraud, E. (Physical Review A, 2016)
Considering C60 as a model system for describing field emission from the extremity of a carbon nanotip, we explore electron emission from this fullerene excited by an intense, near-infrared, few-cycle laser pulse (1013-1014W/cm2, 912 nm, 8-cycle). To this end, we use time-dependent density functional theory augmented by a self-interaction correction. The ionic background of C60 is described by a soft jellium model. Particular attention is paid to the high-energy electrons. Comparing the spectra at different emission angles, we find that, as a major result of this study, the photoelectrons are strongly peaked along the laser polarization axis forming a highly collimated electron beam in the forward direction, especially for the high-energy electrons. Moreover, the high-energy plateau cutoff found in the simulations agrees well with estimates from the classical three-step model. We also investigate the buildup of the high-energy part of a photoelectron spectrum by a time-resolved analysis. In particular, the modulation on the plateau can be interpreted as contributions from intracycle and intercycle interferences.
CRIS-Team Scopus Importer:2023-07-24